Potential of pyrolysis processes in the waste management sector. (September 2017) - Czajczyńska, D.; Anguilano, L.; Ghazal, H.; Krzyżyńska, R.; Reynolds, A.J.; Spencer, N.; Jouhara, H.
Abstract: The fundamentals of pyrolysis, its latest developments, the different conditions of the process and its residues are of great importance in evaluating the applicability of the pyrolysis process within the waste management sector and in waste treatment. In particular the types of residue and their further use or treatment is of extreme interest as they could become the source of secondary raw materials or be used for energy generation in waste treatments. The main area of focus of this paper is the investigation of the link between the pyrolysis conditions, the chemical and mineralogical composition of their products and the benefits of pyrolysis in the waste management sector. More specifically the paper covers the fast, intermediate and slow pyrolysis of organic waste and mixtures of inorganic and organic waste from households. The influence of catalysts during fast pyrolysis on the product yield and composition is not being considered in this review.